Acute cardiovascular complications in a Peruvian population of oncology patients - Valenzuela-Rodríguez, German (2022)
Objective. To know the most frequent acute cardiovascular complications in a Peruvian population of oncologic patients. Materials and methods. Retrospective, descriptive study of oncologic patients treated at Clinica Delgado between January 2014 and December 2019, from which the subgroup with the seven most prevalent cancers at the national level was selected according to information from Globocan 2018. Additionally, we evaluated the epidemiology of patients with cardiovascular complications that conditioned their hospitalization or were detected during this, calculating their cardiovascular risk according to Hermann and SCORE risk scales. Results. Forty-four patients had complications; 27 (61.4%) were hospitalized due to acute cardiovascular causes. The mean age of this subgroup was 69.88 years (SD 12.77), and 22 (81.5%) were older than 60 years. Fourteen (51.9%) were male. According to the Hermann scale, 33.3% had intermediaterisk and 14.9% had a high or very high risk. According to the SCORE scale, 62.97% had an intermediate-risk and 7.40% high risk. The most common acute cardiovascular complications were deep vein thrombosis and ischemic stroke (66.65%). One patient (3.7%) reported previous cardiovascular disease. Four patients (14.8%) had a fatal outcome during hospitalization. The median length of hospitalization was five days. Conclusions. We present the cases of acute cardiovascular complications in a population of oncologic patients and their vascular risk according to Hermann and SCORE scales. The most common complications were deep vein thrombosis (48.14%), stroke (18.51%), and myocardial infarction (14.81%).